EVALUASI IMPLEMENTASI KEBIJAKAN PUBLIK - Dikson Silitonga (ESENSI: Jurnal Manajemen Bisnis, 2018)
In general, this research is aimed at evaluating to what extent the effectiveness of implementation of National Exam policy in mapping and increasing the quality of primary education in Indonesia. By using the Stake’s Countenance evaluation model, this research uses a qualitative and descriptive statistic (simple quantitative) approach with the techniques of data collection through a library study as secondary data sources, deep interviews and observation as primary data sources. On the transaction phase (policy implementation), principally most of the policy have been working in accordance with the regulation, although some of weakness are still found. Weakness in the implementation stage and the unclear follow up improvement over the results of national exam annually by the organizer, gives impact to the unsatisfactory of the national exam policy.